1997
DOI: 10.1021/ie960522g
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Multiple Steady States in Homogeneous Azeotropic Distillation

Abstract: Bekiaris et al. (1993) explained the existence of multiple steady states in homogeneous ternary azeotropic distillation, on the basis of the analysis of the case of infinite reflux and infinite column length (infinite number of trays). They showed that the predictions of multiple steady states for such infinite columns have relevant implications for columns of finite length operated at finite reflux. In this article, experiments are described for the ternary homogeneous system methanol−methyl butyrate−toluene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 14 publications
2
42
0
Order By: Relevance
“…There are three steady-state branches: two stable steady-state branches and an unstable branch; this was experimentally verified in an industrial pilot column operated at finite reflux [23,39]. Multiple steady-states can be predicted by analyzing columns with infinite reflux and infinite length [14,38,64].…”
Section: Background Of the Problemmentioning
confidence: 85%
See 2 more Smart Citations
“…There are three steady-state branches: two stable steady-state branches and an unstable branch; this was experimentally verified in an industrial pilot column operated at finite reflux [23,39]. Multiple steady-states can be predicted by analyzing columns with infinite reflux and infinite length [14,38,64].…”
Section: Background Of the Problemmentioning
confidence: 85%
“…However, all steady-state branches were computed either with the AUTO software package [20] or with an appropriate continuation method [39,46,85]. The initial estimates were carefully chosen with the ∞/∞ analysis [14,38], and special attention was paid to the turning points and branch switching.…”
Section: Published Numerical Results With Continuation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 11, the details of the basic control scheme are described as follows: (1) Feed is flow-controlled (reverse acting); (2) base levels in C 1 and C 2 are held by manipulating the corresponding flow rate of bottom stream (direct acting); (3) reflux drum level in C 1 is held by manipulating distillate flow rate (direct acting); (4) reflux drum level in C 2 is held by manipulating the makeup benzene flow rate (reverse acting); (5) flow rate of stream REC is ratioed to the feed flow rate; (6) top pressures in both columns are controlled by manipulating the corresponding cooling water flow rate in the condenser (reverse acting); (7) reflux ratios in both columns are fixed; (8) temperatures on stage 38 in C 1 and stage 46 in C 2 are controlled by the flow rates of the heating steam into C 1 and C 2 reboilers, respectively (reverse acting).…”
Section: Unstable Operating Point Stabilizationmentioning
confidence: 99%
“…They stated that hysteresis may be experienced during the actual operation. Furthermore, Kienle et al (1995) and Koggersbøl et al (1996) confi rmed the existence of multiple steady states in an experimental way when separating a binary mixture.As regard to azeotropic distillation operations, Güttinger et al (1997) found two stable steady states caused by the vapour-liquid equilibrium for the ternary homogeneous methanol-methyl butyratetoluene system in an industrial pilot column. Besides, Dorn et al (1998) verifi ed the existence of a third unstable steady state and studied the transient behavior of that azeotropic column.…”
mentioning
confidence: 99%